2004
DOI: 10.1152/ajpregu.00159.2004
|View full text |Cite
|
Sign up to set email alerts
|

Glycine intake decreases plasma free fatty acids, adipose cell size, and blood pressure in sucrose-fed rats

Abstract: os. Glycine intake decreases plasma free fatty acids, adipose cell size, and blood pressure in sucrose-fed rats. Am J Physiol Regul Integr Comp Physiol 287: R1387-R1393, 2004. First published August 26, 2004 doi:10.1152/ajpregu.00159.2004The study investigated the mechanism by which glycine protects against increased circulating nonesterified fatty acids (NEFA), fat cell size, intra-abdominal fat accumulation, and blood pressure (BP) induced in male Wistar rats by sucrose ingestion. The addition of 1% glycin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
68
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(86 citation statements)
references
References 51 publications
(46 reference statements)
11
68
3
Order By: Relevance
“…27,28 The second identified amino acid glycine is known to reduce oxidative stress because of an enhancement of the bioavailability of nitric oxide. 22,23 As seen in the partial plot of glycine, an increase of glycine concentrations of ≈150 to 250 µmol/L was closely associated with an improvement of 10-year hypertension-free survival time. A recent study showed that glycine concentrations of around 200 µmol/L are required to activate glycine-gated chloride channels which, inter alia, occur in macrophages, monocytes, and endothelial cells.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…27,28 The second identified amino acid glycine is known to reduce oxidative stress because of an enhancement of the bioavailability of nitric oxide. 22,23 As seen in the partial plot of glycine, an increase of glycine concentrations of ≈150 to 250 µmol/L was closely associated with an improvement of 10-year hypertension-free survival time. A recent study showed that glycine concentrations of around 200 µmol/L are required to activate glycine-gated chloride channels which, inter alia, occur in macrophages, monocytes, and endothelial cells.…”
Section: Discussionmentioning
confidence: 89%
“…Nevertheless, the observed results are supported by recent research indicating that supplementation with serine as well as glycine may have BP-lowering effects. [20][21][22][23] Moreover, antiinflammatory and antioxidant properties were attributed to serine and glycine, 20,[23][24][25][26] which may contribute to protective effects regarding the development of hypertension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Hafidi et al reported that 10 g/l drinking water glycine reduces adipose tissue accumulation and plasma fatty acids. 31) It has been also reported that the content of glycine in soy protein and buckwheat protein, known as an anti-obesity factor, [3][4][5][6] is also higher than that in casein. 32) Both glycine and alanine can readily be metabolized to pyruvate, which has been reported to have an anti-obesity effect.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in abdominal fat was most likely accompanied by a decrease in muscle mass as reported by other groups [39] because body weight did not significantly increase. In our model, we have not determined a difference in muscle mass between the Control and MS rats, but sucrose fed animals have been shown to consume less solid food, which means less protein and mineral intake [40] . Although obesity is a risk factor for sarcopenia, its pathophysiology is complex, and multiple factors, including lifestyle, endocrine, and immunological factors, can play a role.…”
Section: Acta Pharmacologica Sinica Npgmentioning
confidence: 99%